Analysis of MSME Innovation Strategies Before and After the Covid-19 Pandemic (Case Study of Omahan Kepanjen Coffee) - Amelia Setyawati; Rayyan Sugangga; Farij Ibadil Maula; Adelia Rahma (CV. AFDIFAL MAJU BERKAH, 2022)
The phenomenon of the COVID-19 pandemic has resulted in economic sluggishness in various sectors. The sectors affected include the MSME sector. Many business actors experienced a decrease in buyers which resulted in a decrease in sales turnover and many MSMEs closed, but there were still many MSMEs that survived and soon rose. Therefore, it is necessary to have a strategy that can make them continue to survive and increase the income turnover of MSME actors. One approach that can be taken to find opportunities and adapt to the situation is an innovation strategy-based approach. This study aims to explore the ups and downs of MSMEs by analyzing the innovation strategies carried out by MSMEs in the period before and after the Covid 19 pandemic with a case study of the Kepanjen Coffee Omahan business. The results of the study indicate that a business needs to immediately implement innovation management by taking into account the internal and external aspects of the company. The results of the innovation must be able to continue to strengthen the value proposition that can make the business strong in the long term. This can be seen from the Kopi Omahan business journey which implemented 4 types of innovation (product, process, marketing, organization), experienced growth in the pre-pandemic phase, then entered a crisis at the peak of the pandemic, and was able to bounce back when the pandemic began to subside.